Molecular characterization of opportunistic pathogenic zygomycetes - Galgóczy, László (Acta Biologica Szegediensis, 2005)
The term zygomycosis refers to a diverse group of mycotic diseases caused by members of the orders Mucorales and Entomophthorales. These infections are frequently associated with diabetic ketoacidosis, deferoxamine treatment, cancer and its therapy, solid organ or bone marrow transplantations, extreme malnutrition and neutropenia. Although these mycoses are relatively rare, their high mortality rate underline the importance of this group of fungal infections. Molecular techniques are widely used to identify the virulence factors of clinically important fungi or to develop useful diagnostic techniques. However, application of these methods to characterize the opportunistic pathogenic nature of zygomycetes started only a few years ago. This review discusses the current state of molecular studies performed on the pathogenicity and diagnosis of zygomycetes causing opportunistic human mycosis.